Gender stereotypes in visual and verbal texts from government-distributed EFL textbook: Critical discourse analysis - Rama Dwika Herdiawan; Afief Fakhruddin; Eka Nurhidayat; Kardi Nurhadi (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
Research on gender stereotypes in educational materials has been documented. However, research exploring gender stereotype constructions within visual and verbal materials of English as a foreign language (EFL) textbooks remains limited. This study investigates gender stereotype constructions within visual and verbal materials of the Indonesian government-distributed EFL textbook to shape learners' perceptions of gender roles. This study employed critical discourse analysis (CDA) to explore how textbooks construct stereotypical roles through visual depictions, dialogue patterns (verbal), and linguistic characteristics as data sources and verbal ones. The visual and verbal texts were documented in dialogues and analyzed considering theories of gender stereotypes using CDA. The results reveal that males are assigned lucrative and out-of-the-home jobs, like farmers (Beni's father) and teachers (Dayu's dad). In contrast, women are tied to household responsibilities, such as Lisa's mom being a housewife, which confirms the notion that women play a primary role in providing care. This study highlights the significance of employing gender-sensitive teaching strategies to enable EFL students to critically analyze stereotypes and form more expansive understandings of gender roles.